ENOS and nNOS contribution to reflex cutaneous vasodilation during dynamic exercise in humans - McNamara, Tanner (Kansas State University, 2012)
Recent data suggests nNOS mediates the NO-component of reflex cutaneous vasodilation with passive heat stress. Our hypothesis was nNOS, but not eNOS, inhibition would attenuate reflex cutaneous vasodilation during dynamic exercise. Protocol 1: subjects performed a VO[subscript]2 peak test on a supine cycle ergometer. Protocol 2: with experimental arm at heart level subjects cycled in supine posture at 60% VO[subscript]2 peak to raise core temperature (Tc) 0.8-1.0°C (35-45 min). In protocol 2 subjects were equipped with 4 microdialysis fibers on the forearm and each randomly assigned as: 1) lactated Ringer’s (control); 2) 5mM NPLA (nNOS inhibition); 3) 10mM L-NIO (eNOS inhibition); and 4) 20mM L-NAME (non- selective NOS inhibition). At the end of protocol 2 all sites were locally heated to 43°C and infused with SNP to elicit maximal dilation. Mean arterial pressure (MAP), skin blood flow via laser- Doppler flowmetry (LDF), and Tc via ingestible telemetric pill were measured; cutaneous vascular conductance (CVC) was calculated as LDF/MAP and normalized to maximum. In protocol 2 there was no significant difference between control (62±5 %CVCmax) and NPLA (61±6 %CVCmax). L-NIO (38±4 %CVCmax) and L-NAME (41±7 %CVCmax) significantly attenuated CVC compared to control and NPLA (p<0.001 all conditions). There was no difference between L-NIO and L- NAME. We conclude eNOS, not nNOS, contributes to reflex cutaneous vasodilation during dynamic exercise.
Keywords: Cutaneous; Vasodilation; Skin; Endothelial nitric oxide; Neuronal nitric oxide; Exercise; Kinesiology (0575)